Rhythmic patterns of the Peruvian vals criollo and its adaptation to string quartet - Pacheco Belevan, César Alberto (2018)
Knowing that traditional valscriollo instruments are the guitar, cajón drum and voice, the present paper analyzes how this musical genre’s rhythmic patterns can be adapted in elaboration of arrangement for string quartet. In order to get that, a musical analysis of the rhythmic patterns was made since musical performance in cajón drum and, in relation to them, an analysis of rhythmic-harmonic rifs traditionally performed in the accompaniment of the guitar. So, the center of this work is to demonstrate how the guitar voices are distributed among the instruments of the quartet, in such a way that the typical texture and rhythmic structure of the vals criollo were preserved. Since this project is oriented to artistic works, the case in this paper is the waltz Callejón de un solo caño.